Pollutant Pb burden in Mediterranean Centroscymnus coelolepis deep-sea sharks. (January 2022) - Veron, A.; Dell'Anno, A.; Angelidis, M.O.; Aloupi, M.; Danovaro, R.; Radakovitch, O.; Poirier, A.; Heussner, S.
Abstract: We report lead (Pb) analyses in juvenile ( n  = 37; mean length = 24.7 ± 2.3 cm) and adult ( n  = 16; mean length = 52.3 ± 9.3 cm) Centroscymnus coelolepis Mediterranean deep-sea sharks that are compared to Pb content in bathy-demersal, pelagic and shallow coastal sharks. Median Pb concentrations of C. coelolepis muscle (0.009–0.056 wet ppm) and liver (0.023–0.061 wet ppm) are among the lowest encountered in shark records. Stable Pb isotope imprints in adult C. coelolepis muscles highlight that most of Pb in C. coelolepis is from human origin. Lead isotopes reveal the persistence of gasoline Pb emitted in the 1970s in low-turnover adult shark's muscle while associated liver imprints are in equilibrium with recent pollutant Pb signatures suggesting an efficient pollutant Pb turnover metabolism. The comparison of Pb distribution between adult and juvenile cohorts suggests the role of dietary exposure and possible maternal offloading of Pb during gestation, likely associated to vitellogenesis in this aplacental viviparous deep-sea shark. Highlights: Lead content of Mediterranean deep-sea C. coelolepis is among the lowest encountered in sharks from various habitats Pb isotope imprints reveal that Pb is mainly from anthropogenic origin in C. coelolepis tissues In spite of its significant decline in European atmosphere, gasoline Pb remains prevalent in adult C. coelolepis muscles Dietary and possible maternal offloading contribute Pb burden in C. coelolepis muscle (adults) and liver (juveniles)